2022
DOI: 10.1021/acs.jchemed.1c00999
|View full text |Cite
|
Sign up to set email alerts
|

How Participation in a Research Experiences for Undergraduate Program Transforms Chemistry and Biochemistry Majors’ Understanding of Research and Scientific Inquiry

Abstract: Little is known concerning chemistry and biochemistry majors' understanding of research and scientific inquiry. In this three-year qualitative research study, chemistry and biochemistry majors were interviewed before and after participating in a National Science Foundation-sponsored Research Experiences for Undergraduates (REU) program at a private urban research university in the Northeastern United States to learn about their conceptions of research, its purpose, and process. Participation in undergraduate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…Moreover, the students who carry out their projects in other universities or research centers always indicate that they have no problems when integrating into the research groups. These data agree with the observations of Kolon et al 22 and Lopatto. 23…”
Section: Advantages and Disadvantages Of The Pedagogical Approach Usedsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, the students who carry out their projects in other universities or research centers always indicate that they have no problems when integrating into the research groups. These data agree with the observations of Kolon et al 22 and Lopatto. 23…”
Section: Advantages and Disadvantages Of The Pedagogical Approach Usedsupporting
confidence: 94%
“…Although the main goal of this paper is the outcome “Research Skills”, classified as systemic in the Tuning Project, it is also intended to expose the overall design strategy of the entire curriculum in terms of experimental subjects. Different authors have studied the use of inquiry-based experiments in the teaching of various subjects, such as general chemistry, ,, biochemistry, physical chemistry, environmental and analytical chemistry, and organic chemistry . However, this paper analyzes the use of this philosophy throughout a degree’s curriculum, involving and interconnecting all experimental subjects of Chemistry and Chemical Engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In a study in chemistry, Kolon and Mabrouk found that a research program for undergraduates enhanced their understanding of how and why research is conducted as well as the fundamental human nature of research and the role of failure in research. 17 Searching for literature and using the appropriate databases to answer research questions has also been explored in the context of CER. 18 Finally, communicating about science is important when results are research-based.…”
Section: ■ Introduction and Backgroundmentioning
confidence: 99%
“…For example, the use of augmented and virtual reality tools to visualize large, complex molecules has been described, including the use of molecular dynamics in the process . Biochemistry has also been a core component of several publications related to research, including course-based undergraduate research experiences (CUREs) and their impacts. Finally, the interdisciplinary proclivity of teaching innovation in biochemistry includes considerations of bioethics as an important part of student learning …”
mentioning
confidence: 99%